The typical site conception of scientific library entering the structure of LNS RAS - A. A. Ivanovsky (Библиосфера)
A typical site of a scientific library entering the structure of the Library for Natural Sciences of the Russian Academy of Sciences (LNS RAS) is aimed to meet information needs of a certain scientific team - employees of scientific institutions served by a particular library. The main function of the site is to permit the user visiting the library virtually with both information and reference purposes. The site concept assumes compatible technology of its creation with ready software of LNS RAS and simple methods of content updating available to non-specialists in programming.